ANALISIS DAMPAK LINGKUNGAN DAN PENETUAN STRATEGI GREEN MANUFACTURING PADA PENGOLAHAN LIMBAH DAN EMISI DI PT. XYZ - Salman Al Farizy; Adianto; Carla O Doaly (Jurnal Mitra Teknik Industri, 2025)
The manufacturing industry contributes significantly to carbon emissions and environmental pollution, particularly in the production of carbon rods. PT. XYZ, as a carbon rod manufacturer, faces challenges in managing CO₂ emissions and solid waste efficiently. This study aims to analyze environmental impacts and formulate appropriate Green Manufacturing strategies to support sustainable waste and emission management. The methods used are SWOT analysis to identify internal and external factors, and the Analytical Hierarchy Process (AHP) to determine strategic priorities based on ISO 14001 criteria. The results show that the most suitable strategy is the Strength–Opportunity (SO) approach with a total weight of 4.62, which focuses on optimizing baking process facilities and collaborating with certified waste treatment partners to reduce emissions and environmental impact